PELATIHAN PROFESIONAL PERBANKAN PADA PT. BANK PERKREDITAN RAKYAT UKABIMA KHATULISTIWA PONTIANAK - Pieter Gunawan; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2019)
AbstractThe focus in this study was to analyze: (1) Forms of implementing professional training; (2) Impact of professional training on improving employee service skills; (3) Factors constraining the implementation of professional training; & (4) Solutions to overcome factors that constrain the implementation of professional training. This study used a qualitative approach, this research was conducted at PT. Equity Bank Credit Bank Ukabima Pontianak. The research subjects were all 13 employees. The technique of collecting data was in-depth interviews with Focus Group Interview (FGI) and documentary studies. The results of the study indicate the following: (1) The form of implementation of banking professional training consists of credit training and operational training; (2) Training of banking professionals has an impact on: (a) increasing employee motivation; (b) the ability to find alternative solutions to problems; (c) Increased employee confidence in performing services to customers; & (d) calm in solving problems; (3) Factors constraining the implementation of professional training consist of: (a) short training time; (b) coach language which tends to be